DECENTRALIZATION ON DEVELOPMENT IN DEVELOPING COUNTRIES (Comparative Study of Makassar City and Ulsan City) - Farid, Miftah; Luneto, Riska (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2024)
Decentralization experiences were quite different in each country. This difference can be seen in the authority given to local governments, which has an impact on development efforts produced by local governments. This research uses the concept of decentralization in looking at development in Indonesia and South Korea. The differences in the implementation of decentralization in the two countries can then be explained by the development carried out by the local governments of Makassar City and Ulsan City. Indonesia and South Korea have several differences in the formation of the decentralized system and the implementation of the decentralized system in each country. This shows that in the development process, both have different roles and influences, Makassar emphasizes foreign cooperation which is dominated by infrastructure development and human resource development, while Ulsan has a fairly high intensity of foreign cooperation and prioritizes foreign cooperation in the industrial sector with export-oriented, this shows the difference in policy influence provided by the two cities.